Effects of Pinealectomy and Short Day Lengths on Reproduction and Neuronal RFRP-3, Kisspeptin, and GnRH in Female Turkish Hamsters. (June 2014) - Piekarski, David J.; Jarjisian, Stephan G.; Perez, Luz; Ahmad, Huzaifa; Dhawan, Namita; Zucker, Irving; Kriegsfeld, Lance J.
Long days (LDs) stimulate and short days (SDs) inhibit reproduction in photoperiodic rodents by modifying nocturnal pineal melatonin secretion. In LD Turkish hamsters, unlike other rodents, pinealectomy induces reproductive quiescence comparable to that produced by SDs. We assessed whether SDs and pinealectomy induce similar or different patterns of kisspeptin and gonadotropin-inhibitory hormone (also known as RFamide-related peptide-3 [RFRP-3] in mammals) expression, important mediators of seasonal reproductive changes in other species. Brains were harvested from sham-operated female Turkish hamsters maintained in LDs and SDs and LD-pinealectomized (pinx) females, all housed in their respective photoperiods for 12 weeks. Uterine weights were substantially higher in LD-sham than in LD-pinx and SD-sham females. RFRP-3-immunoreactive(-ir) cells in the dorsomedial hypothalamic nucleus were greater in number and size in the reproductively competent LD-sham hamsters than in both reproductively suppressed SD-sham and LD-pinx hamsters. LD-sham hamsters had more kisspeptin-ir cells in the anteroventral periventricular nucleus than did LD-pinx hamsters. Reproductive quiescence, whether induced by short-day lengths or pinealectomy, was generally accompanied by comparable changes in RFRP-3 and kisspeptin, suggesting that long-duration melatonin signaling and withdrawal of melatonin by pinealectomy may act through the same neural substrates to induce gonadal quiescence.